Gallic Acid Improves Health‐Associated Biochemical Parameters and Prevents Oxidative Damage of DNA in Type 2 Diabetes Patients: Results of a Placebo‐Controlled Pilot Study. Issue 4 (15th January 2018) - Ferk, Franziska; Kundi, Michael; Brath, Helmut; Szekeres, Thomas; Al‐Serori, Halh; Mišík, Miroslav; Saiko, Philipp; Marculescu, Rodrig; Wagner, Karl‐Heinz; Knasmueller, Siegfried
Abstract : Scope: Oxidative imbalance plays a key role in cancer induction and cardiovascular diseases (CVD) in patients with type 2 diabetes mellitus (T2DM). The aim of this study is to find out if gallic acid (GA) prevents oxidative stress in diabetic patients. Therefore, we investigate its impact on oxidation of DNA bases and on other health‐related macromolecules. Methods and results: We perform an intervention study ( n  = 19) with GA and monitored alterations of the DNA stability in single cell gel electrophoresis (SCGE) assays in lymphocytes. Furthermore, a panel of health‐related biomarkers is measured before and after consumption of GA (15 mg p –1  d –1 ) for 7 d. Significant reduction of oxidized purines (by 31%, p <  0.001, effect size 0.404) and pyrimidines (by 2%, p <  0.022, effect size 0.089) is observed in SCGE assays. Furthermore, the plasma concentrations of oxidized‐LDL and C‐reactive protein are reduced after the intervention by 24% ( p =  0.014, effect size 0.384) and 39% ( p <  0.001, effect size 0.686), respectively. No alterations of other biomarkers are found. Conclusions: A small amount of GA (in the range of daily consumption in Central Europe) prevents oxidative DNA damage and reduces markers which reflect inflammation and increased risks of cancer and CVD. Abstract : Gallic acid (GA) supplementation over 7 d reduced oxidized purines in lymphocytes of T2DM patients. Oxo‐LDL was reduced by 24% in plasma after supplementation with GA. C‐reactive protein was reduced by 39% in plasma after supplementation. GA may contribute to the prevention of diabetes associated diseases.